Sequential systematic anti‐mold prophylaxis with micafungin and voriconazole results in very low incidence of invasive mold infections in patients undergoing allogeneic hematopoietic stem cell transplantation. Issue 4 (7th May 2018) - Rosillo, Claudia; Avila, Ana Maria; Huang, Yao‐Ting; Devlin, Sean; Cho, Christina; Montoro, Juan; Maloy, Molly A.; Papanicolaou, Genovefa A.; Barba, Pere; Perales, Miguel‐Angel
Abstract: Recipients of allogeneic hematopoietic stem cell transplantation (allo‐HSCT) are at high risk for invasive mold infections (IMI). The goal of the study is to describe the incidence and outcome of IMI in patients after allo‐HSCT in a large cohort of patients receiving anti‐mold prophylaxis. We conducted a retrospective review of 988 consecutive adults who underwent allo‐HSCT in our center from 2008 through 2014. Standard prophylaxis consisted of micafungin 150 mg IV daily from admission to day +7 ± 3 followed by voriconazole until day +75 to +100. Cases meeting criteria for proven or probable IMI according to EORTC‐MSG criteria were included. Median age at HSCT was 54 years. The most common diagnoses were acute myeloid leukemia (n = 351, 36%) and lymphoid malignancies (n = 248, 25%). Matched related or unrelated donors (URD) were used in 686 (69%) patients, mismatched URD in 142 (14%) and cord blood units in 154 (16%). Twenty‐one patients were diagnosed with IMI after allo‐HSCT, 19 probable and 2 proven, and one patient was diagnosed postmortem. Microbiological diagnosis was established in 9 cases, 5 of them being Aspergillus . One‐year cumulative incidence (CI) of IMI was 1.6% (95% CI 0.9‐2.5) while 12‐week overall survival after IMI was 39% (95% CI 24‐65) Analyzed by disease, there was a trend for a higher 1‐year CI of IMI in patients with ALL (5% [95% CI 1.6‐11.4]) when compared with AML (1.4%), MDS (1.5%) and lymphoma (1.2%), P  = .06. The 1‐year CI of IMI after transplantation is low in patients receiving anti‐mold prophylaxis with micafungin bridged to voriconazole, although these infections are associated with a higher risk of mortality.